Origin and Development of Moral Sense: A Systematic Review - Limone, Pierpaolo; Toto, Giusi Antonia (Frontiers in Psychology, 2022)
The literature suggests that the moral sense is based on innate abilities. In fact, it has been shown that children show the capacity for moral discernment, emotions and prosocial motivations from an early age. However, the moral sense is a complex construct of an evolutionary and social nature that evolves under the influence of interpersonal relationships. Objective The emergence and development of moral sense is a challenge that has prompted many research studies with the aim of achieving a clear comprehension of moral development. However, success has been scarce, and studies relevant to this subject are limited. Thus, a systematic review of studies relevant to this topic was conducted to clearly establish how moral sense emerges and develops. Methods An Ovid search was conducted to retrieve relevant items for this systematic review. The databases that were electronically visited are Cross-reference, Google Scholar and PubMed. Strict inclusion and exclusion criteria were imposed on the retrieved items to retain only relevant resources. Results Twenty-six studies were found valid for inclusion in this systematic review. The results of these studies were presented differently: In order to effectively analyze the selected papers and bring out the results more clearly, a categorization of the approaches adopted in the studies was carried out. The approaches identified were: “Natural Moral Sense”, “Social Relationships and Moral Development”, and “Environmental Factors and Moral Development”. The evidence that emerged from the analysis of the papers was collected to produce a general basic model that explains moral development while also serving as a link between the various studies. First, moral sense is found to be innate in humans; individuals can naturally respond morally to various dilemmas. As seen among children and young infants, moral sense naturally exists. Second, it can be socially nurtured through social interactions and exposure to various environmental factors. Conclusion Various research studies were reviewed in this systematic review to obtain a consensus on how moral sense emerges and develops. From the systematic review, the moral sense is found to be innate. However, moral development is fostered by social interactions and environmental factors.